Evaluation of antibacterial properties of triorganotin carboxylates containing functionalised ester groups in tests against some pathogenic bacteria - Koshy, J.; Ansary, A.; Lo, K.M.; Das, V.G. (Hindawi Publishing Corporation, 2001)
Bacterial screening employing the agar diffusion test on triphenyltin carboxylates containing various functional residues in the ester moiety revealed appreciable differences in their activities relative to triphenyltin acetate. Among these, [3-(Diethylphosphono)propionato] triphenyltin (1) and [N-cyclohexylcarbamoyl) glycinato] triphenyltin displayed activities comparable to tri-n-butyltin cinnamate (2) towards both Gram-positive and Gram-negative bacteria; the latter compound was the most active among the eleven triorganotin compounds tested, which included cyclopentyldiphenyltin hydroxide (3) and its methacrylate derivative. Applying the more quantitative plate count and optical density tests on compounds 1-3, it was shown that their inhibitory activity ranked in the order 2 > 3 >1. Significantly, 3 caused around 90% inhibition of both Eschechia coli (-) and Pseudomonas aeruginosa (-) when incubated for 24 h at 37+/-1 at the 10.0 mug/ mL concentration level. Compound 2 was less effective against P.aeruginosa than against E.coli. While the Gram-positive bacteria were all readily inhibited, Bacillus subtilis (+) appeared to the most susceptible among them towards the test compounds.